Who is the Subject in Educational Research? - Alicia Gurdián-Fernández (Universidad Nacional, Costa Rica, 2011)
In this paper I argue, first, that the identity of the researcher has an impact not only in the way she/he invThis article explains, in the first place, that the identity of the researcher not only influences his way to do research, but also the teaching processes and, therefore, training of future researchers. Secondly, it states that schools and teachers play a central role in the construction of identities. Third, this paper emphasizes that those engaged in educational research are not released from this responsibility, so this is an invitation to reflect on the following: What are our responsibilities in the process of identity construction? Who is the subject of education? Who is the subject of educational research? How inclusive is our notion of both the educational and the empirical subjects? Through the analysis of questions on topics such us: the subject-object relationship; the subject in educational research; the contribution of subjectivity; the contribution of phenomenology; among others, this paper explains that: a) the intellectual autobiography is a great potential instrument to understand the direction of a research process and b) focusing on people, their history, social relationships and environment, as subjects and not just as objects of study, is an epistemological, political and ethical movement, which recognizes the subject's action in and on the world. Finally, this paper states that qualitative researchers should not only understand who they are, they are ethically obliged to make it explicitly.